The Formation of Special Electoral Court Institution: Between Democratization of Regional Head Elections and Institutional Issues - Herman Harahap (CERED Indonesia Institute, 2022)
The separation between the patterns of resolving election disputes and the separation of institutions for resolving election disputes will ultimately lead to potential legal uncertainty, prolonged settlement, and even dualism of election dispute resolution institutions. Therefore, a more integrative approach is needed in resolving election disputes which includes the idea of forming a special electoral court institution. However, the discourse on the formation of a special electoral court institution requires further discussion regarding the position of the intended special judicial institution, whether it falls within the jurisdiction of the Constitutional Court or the Supreme Court. The research method used in this study is normative legal research with a legislative approach and a case approach. Given the complexity of the law in resolving local election disputes which are separated into process disputes and results disputes, an integrative special judicial body is indeed needed to examine and decide on election disputes, not only limited to election results, but also covering all aspects of the election. Essentially, democratization of regional head elections as previously described also includes reforming local election regulations, including legal means for resolving election disputes that provide legal certainty. In this regard, one option is to establish a special local election court or a special electoral court in general.